Usage model-based automated testing of C++ templates. - Sayre, Kirk (Software engineering notes.)
The object-oriented design of software in C++ using class templates presents many advantages over non-object-oriented or non-template based software design. However, the testing of template based C++ software involves some unique issues not usually faced during the testing of non-template based software. This paper will describe these testing issues and describe a proposed solution to these issues using a usage model-based automated testing framework.